Decision Support System To Choose The Best Social Media Platform For Product Marketing Using Topsis Method - Putri, Dwi Andini; Alawiah, Enok Tuti (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Currently, many content creators use social media to conduct product reviews or testimonials. This often attracts followers to make purchases of the same product. Marketing of products with social media is mostly done by the industry to attract buyers. However, in-depth research is needed to analyze which social media is most appropriate to use to market their products. This study uses the TOPSIS method, which is a multi-criteria selection method that uses a positive and negative ideal solution distance approach to obtain a valid final preference value. The results showed that as many as 0.31 social media youtube, 0.24 for social media tiktok, 0.20 for social media instagram and 0.11 for social media facebook. The results of the study can be used by policy makers to decide the selection of the right social media for marketing their products